2021
DOI: 10.3310/pgfar09050
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of vascular services: a multiple methods research programme

Abstract: Background Vascular services is changing rapidly, having emerged as a new specialty with its own training and specialised techniques. This has resulted in the need for reconfiguration of services to provide adequate specialist provision and accessible and equitable services. Objectives To identify the effects of service configuration on practice, resource use and outcomes. To model potential changes in configuration. To ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 175 publications
0
8
0
Order By: Relevance
“…Coding of procedures and other information is restricted and may change over time. In identifying and classifying procedures there may be conflicting or non-specific codes, and the algorithms used to deal with such circumstances have been developed and described elsewhere 3 . Some codes may cover several different procedures, such as those for sclerotherapy, which may be for axial veins or tributary treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Coding of procedures and other information is restricted and may change over time. In identifying and classifying procedures there may be conflicting or non-specific codes, and the algorithms used to deal with such circumstances have been developed and described elsewhere 3 . Some codes may cover several different procedures, such as those for sclerotherapy, which may be for axial veins or tributary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found the treatment of symptomatic VVs to be both clinically effective and highly cost-effective in the terms usually used by the NHS 3 , 9 , 25 , 26 . Despite national guidance from NICE having accepted this, and having recommended interventional treatment for symptomatic people, the condition is considered relatively minor and therefore has become an easy target for rationing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations